Empleo de modelos cartográficos tridimensionales aplicados al estudio Histórico-Artístico del Territorio - José Ramón Ruiz Checa; Valentina Cristini; Mª Isabel Sánchez Duque (Virtual Archaeology Review)
In Cuenca district, Spain, at only 150kms south east from Madrid we can find a dense net of watchtowers, dated on the last years of the XII century, scattered all over the territory. These enigmatic constructions, following the results of the presented, research have a Christian origin, due to their control of the territory and bonded with the regulation of the displacements of livestock during the seasons. Have they a military or a civil function? Both of the possibilities are documented… morphological and typological studies have been developed with special attention to cartographical 3d models. The research has opened an interesting horizon about the relations between territory, towers and historical paths, visible in the district during the Reconquest Ages. In conclusion, use of territorial models for archeological research.